Status Hukum Perjanjian Internasional dalam Hukum Nasional RI Tinjauan dari Perspektif Praktek Indonesia - Agusman, Damos Dumoli (Indonesian Journal of International Law, 2008)
It is always interesting to compare between academic analysis and practical matter in implementing treaties in Indonesia. This article tries to overview treaties and its relevant affairs from practical perspective which of course will enrich the discussion of treaty implementation and pinpoint what aspects should be further scruitnized.